1989
DOI: 10.4315/0362-028x-52.3.154
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Procedures to Detect Listeria spp. in Foods

Abstract: A comparison was made of four procedures to detect Listeria spp. in two food categories. The study comprised 309 assays, 71 on milk from both infected and uninfected cows, and 238 on ten types of fresh vegetables. A sample was considered positive if it could be detected by at least a single method and if isolates could be confirmed as Listeria spp. The procedures detected 98–100% of the positive milk samples. Recovery from vegetable samples ranged from 45 to 86%, probably because of low levels of Listeria spp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Published studies have examined the incidence and fate of L. monocytogenes in fresh vegetables (Beuchat, 1996;Petran et al, 1988). In two surveys of fresh market produce, L. monocytogenes was detected on 27.1% (Heisick et al, 1989a) and 25.8% (Heisick et al, 1989b) of potato samples tested. The organism has been isolated from the feces of animals (Weis and Seeliger, 1975) which may be a potential source of fresh produce contamination (Schlech et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Published studies have examined the incidence and fate of L. monocytogenes in fresh vegetables (Beuchat, 1996;Petran et al, 1988). In two surveys of fresh market produce, L. monocytogenes was detected on 27.1% (Heisick et al, 1989a) and 25.8% (Heisick et al, 1989b) of potato samples tested. The organism has been isolated from the feces of animals (Weis and Seeliger, 1975) which may be a potential source of fresh produce contamination (Schlech et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Others have isolated it from corn and grain plants, lettuce, parsley, and watercress (46, 58). Many studies have indicated that L. monocytogenes can grow or survive on fresh or processed produce, including asparagus, broccoli, cauliflower, and leafy vegetables, and it has been isolated from many prepared salads (9,16,22,28,35). The only types of produce that seem to inhibit growth or kill L. monocytogenes are tomatoes and carrots (11,42).…”
mentioning
confidence: 99%
“…Some of these tests have been applied to pathogens of a bovine origin, such as the Minitek GramPositive Set for Streptococcus (29), but with no success because of a lack of information on veterinary pathogens in the database. Enzyme-linked immunosorbent assay methods exist for S. aureus detection in cases of BM (10), but the antibody titer does not correlate with the amount of infecting bacteria (10,15). Other enzyme-linked immunosorbent assays were developed to screen milk for contamination with Listeria organisms (1,9).…”
mentioning
confidence: 99%